2021
DOI: 10.1002/pra2.441
|View full text |Cite
|
Sign up to set email alerts
|

Not Quite ‘Ask a Librarian’: AI on the Nature, Value, and Future of LIS

Abstract: AI language models trained on Web data generate prose that reflects human knowledge and public sentiments, but can also contain novel insights and predictions. We asked the world's best language model, GPT-3, fifteen difficult questions about the nature, value, and future of library and information science (LIS), topics that receive perennial attention from LIS scholars. We present highlights from its 45 different responses, which range from platitudes and caricatures to interesting perspectives and worrisome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…library discovery tools), or what impact the systems (and their many well‐established biases) will have on European society. A paper presented at ASIS&T 2021 suggested that because GPT‐3 already generated plausible but false content, future iterations might "drastically change the nature of everyday information retrieval… with serious social and ethical” consequences (Dinneen & Bubinger, 2021, p. 10). With ChatGPT and its contemporaries, that future is now, and society is in an uncharted information frontier.…”
Section: Panel Format (90 Minutes)mentioning
confidence: 99%
“…library discovery tools), or what impact the systems (and their many well‐established biases) will have on European society. A paper presented at ASIS&T 2021 suggested that because GPT‐3 already generated plausible but false content, future iterations might "drastically change the nature of everyday information retrieval… with serious social and ethical” consequences (Dinneen & Bubinger, 2021, p. 10). With ChatGPT and its contemporaries, that future is now, and society is in an uncharted information frontier.…”
Section: Panel Format (90 Minutes)mentioning
confidence: 99%